Andrei Sakharov’s research work and modern physics - Altshuler, B L (Physics Uspekhi, 2021)
We follow the work carried out by Andrei Sakharov in both research and engineering, from the first domestic thermonuclear charges to fundamental physics. We emphasize the current status of the research fields recognized to have originated in Sakharov’s work: controlled fusion, magnetic cumulation and magnetic explosion generators, induced gravity, cosmological ‘Sakharov’ (baryonic acoustic) oscillations, and baryon asymmetry of the Universe. Another subject that unexpectedly gained momentum in the 21st century is the model of a pulsating universe, which was among Sakharov’s ideas. Other subjects that were dear to him, such as quantum cosmology and the anthropic principle, are also currently at the forefront of science.